Valuation of hydrodynamic instabilities in inertial confinement fusion target in a magnetic field - Kuzenov, V.V.; Ryzhkov, S.V. (Вопросы атомной науки и техники, 2013)
Magneto-inertial fusion (MIF) or inertial confinement fusion with magnetized target implosion is considered. Laser-driven MIF allows to compress the preseeded magnetic field to thousands of teslas. Model of high pulse energy laser target interaction is presented. Richtmyer-Meshkov (R-M) instability is investigated for MIF systems. We have shown that there is a possibility to suppress the R-M instability by magnetic field. Modeling the impact of magnetic field on a single plasma jet formed at the ICF laser target compression is performed. It is shown that at the compression and heating of a plasma target by using a rapidly growing external magnetic field and laser radiation the R-M instability can be suppressed.